Advances in Design for Inclusion Proceedings of the AHFE 2016 International Conference on Design for Inclusion, July 27-31, 2016, Walt Disney World®, Florida, USA - Di Bucchianico, Giuseppe; Kercher, Pete.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book focuses on a range of topics in design, such as universal design, design for all, digital inclusion, universal usability, and accessibility of technologies independently of people's age, economic situation, education, geographic location, culture and language. It especially focuses on accessibility for people with auditory, cognitive, neurological, and visual impairments, ageing populations, and mobility for physical special needs. The book explores some of the overlaps between inclusive design and web accessibility to help managers, designers, developers, policy makers, and researchers optimize their efforts in these overlapping areas. Based on the AHFE 2016 International Conference on Design for Inclusion, held on July 27-31, 2016, in Walt Disney World®, Florida, USA, this book discusses new design technologies, highlighting various requirements of individuals within a community. Thanks to its multidisciplinary approach, the book represents a useful resource for readerswith different kinds of backgrounds and provides them with a timely, practice-oriented guide to design for inclusion.
Design for Inclusion and Product Development -- Designing for Inclusion in the Public Sector and Cultural Heritage -- Design for Disability and Social Inclusion -- Designing for Inclusion: Methodology and Future Trends -- Multisensory Design and Mobility for Special Needs -- Inclusive and Universal Fashion Design in Clothing, Footwear and Accessories -- Design for Inclusion: The Japanese Perspective -- Designing for Inclusion in Learning Experiences -- Designing for Inclusion for Ageing Population -- Designing for Inclusion in the Information Society -- Dissing the Dis - The Swedish Concept -- Design for Inclusion in the Living Environment and Ageing Population.
Keywords: Computational intelligence; Engineering design; Industrial design; Cognitive psychology; Computational Intelligence; Engineering Design; Industrial Design; Cognitive Psychology